Efektivitas Model Pembelajaran Project Based Learning dalam Pengembangan Kompetensi Manajemen Sumber Daya Manusia di STIKOM Tunas Bangsa - Zulia Almaida Siregar; Dedi Suhendro; Rizki Alfadillah Nasution; Abdi Rahim Damanik (Departement of Mathematics Education, 2025)
This study aims to measure the effectiveness of the Project Based Learning (PBL) model in developing human resource management (HRM) competencies. The research method used was experimental with a pretest-posttest control group design. The research sample consisted of two groups of students: the experimental group that used the PBL model and the control group that used conventional methods. Data were collected through competency tests, observation sheets, and questionnaires. The results showed that the experimental group experienced a more significant increase in average scores from pretest to posttest compared to the control group. Additionally, observations revealed that the level of student engagement in PBL-based learning was higher than in conventional methods. Questionnaire analysis revealed that 85% of students responded positively to PBL, considering it more relevant to the professional world and capable of enhancing critical thinking and collaboration skills. In conclusion, the PBL model proved effective in improving HRM competencies, both in terms of conceptual understanding and practical skills. It is recommended that this model be more widely integrated into learning to support the development of competent and job-ready graduates.